2020
DOI: 10.1111/ene.14382
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of neurological manifestations of SARS‐CoV‐2 infection: the devil is hidden in the details

Abstract: All authors are members of the Infectious Disease Panel of the European Academy of Neurology (EAN). PT and JS are the co-chairs. The Chair of the Scientific Committee of the EAN approved the addition of the phrase "for the Infectious Disease Panel of the EAN".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 49 publications
6
94
1
14
Order By: Relevance
“…examined but, nevertheless, we can rule out a systematic and important infection of the brain following SARS-CoV-2 infection in hamster. This is consistent with a recent review of the literature which failed to indicate any central nervous manifestation of SARS-CoV-2 presence in human central nervous system (Romoli et al, 2020), however the neurotropic ability of SARS-CoV-2 remains controversial (Wang et al, 2020). Interestingly, SARS-CoV-1 has been shown to be neurotropic only using ACE2 humanized mice.…”
Section: Discussionsupporting
confidence: 89%
“…examined but, nevertheless, we can rule out a systematic and important infection of the brain following SARS-CoV-2 infection in hamster. This is consistent with a recent review of the literature which failed to indicate any central nervous manifestation of SARS-CoV-2 presence in human central nervous system (Romoli et al, 2020), however the neurotropic ability of SARS-CoV-2 remains controversial (Wang et al, 2020). Interestingly, SARS-CoV-1 has been shown to be neurotropic only using ACE2 humanized mice.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, the characteristic pattern of stroke in individuals with COVID-19, with an increased proportion of large artery occlusion, infarction involving multiple territories, and increased cryptogenic aetiology, suggests a causal relationship in at least a proportion of patients.Previous reports have been published with the attempt to clarify the relationship between stroke and COVID-19. These included narrative reviews(32,33), systematic reviews(9)(10)(11)34) and metaanalyses(34,35). While some authors have focused on the relationship between personal history of CVD and COVID-19(7, 8), we studied the incidence and risk factors for the occurrence of new CVD in concomitant SARS-CoV2 infection, searching for a specific profile of COVID-19associated stroke.…”
mentioning
confidence: 99%
“…Kremer et al retrospectively reviewed the characteristics of 64 confirmed COVID-19 patients with neurological complications, who underwent a brain MRI; encephalitis was one of the most common neuroimaging finding (17%); moreover, patients with encephalitis were younger. In this work, the Authors were incline to accept the autoimmune/inflammatory theory, due to the absence of the virus in cerebrospinal fluid and the presence of signs of inflammation in both neuroimaging and cerebrospinal fluid 29 to check for intrathecal humoral immune reaction 32 . Moreover, recently the presence of SARS-CoV-2 RNA in the cerebrospinal fluid has been detected by genome sequencing in a patient with clinically proved meningoencephalitis in Japan 33 .…”
Section: Discussionmentioning
confidence: 99%